Comparison of cytokine/chemokine profiles between dermatomyositis and anti-synthetase syndrome - Wang, Yikang; Zheng, Yiming; Zhao, Yawen; Liu, Yilin; Zhang, Wenhao; Yu, Meng; Xie, Zhiying; Hao, Hongjun; Gao, Feng; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun (Frontiers in Neurology, 2022)
Objectives Dermatomyositis (DM) and anti-synthetase syndrome (ASS) are autoimmune diseases with multisystem involvement. Despite sharing some clinical and myopathological features, these are two diseases with different pathogeneses and prognoses. We aimed to clarify and compare cytokine/chemokine profiles in both disorders, which may help in the differential diagnosis. Materials and methods We collected clinical data and serum samples of consecutive patients with DM and ASS. Quantibody® Human Inflammation Array 3 for cytokines/chemokines was performed in the serum of all participants. Receiver operating characteristic analysis with the area under the curve and Youden's index were performed. Results Eight newly diagnosed and treatment-naïve patients with DM, nine newly diagnosed and treatment-naïve patients with ASS, and 14 healthy controls were enrolled. Serum C-C motif chemokine ligand (CCL) 2, CCL4, C-X-C motif chemokine ligand (CXCL) 13, and tumor necrosis factor receptor 2 (TNFR2) were increased in patients with both DM and ASS. Serum interleukin (IL)-1 receptor type 1 (IL-1ra), IL-1b, CCL1, CXCL11, and CCL3 were modulated in patients with DM only, and IL-8, CXCL9, and tissue inhibitors of metalloproteinases-1 (TIMP-1) in patients with ASS only. Serum CCL2, CXCL13, and TNFR2 accurately distinguished patients with DM and ASS from healthy controls, as shown by the area under the curve >0.80. Moreover, receiver operating characteristic analysis showed that, as biomarkers for discrimination between DM and ASS, the combination of IL-1ra and TIMP-1, had an area under the curve of 0.944, a sensitivity of 87.5%, and a specificity of 88.9%. Conclusion Our study demonstrated that serum levels of cytokines/chemokines showed a different pattern in newly diagnosed patients with DM and ASS, in which serum IL-1ra and TIMP-1 could be used to distinguish between the two diseases.